The invisible power of the invisibles: A study of the efficacy of Narradrama method in assisting South African domestic workers in shifting their self-identity - Yarmarkov, Hanna (My University, 2016)
The aim of this research was to evaluate Narradrama as a drama therapy method in assisting South African domestic workers to shift their identity towards a more positive one, so they will be able to better deal with their current socially oppressive issues. I postulated, based on research done by sociologists and anthropologists, that domestic workers still feel oppressed marginalised and differentiated even to date, twenty years after the apartheid era; the racial discrimination that was perpetuated by the doctrine of the apartheid regime and cemented the master-servant relationship as the only possible relationship between domestic worker and employer was normalised within the harsh realities of minimum wages, long working hours and appalling living conditions; oppression of women by women, sexism and racism. Moreover, the domestic workers legal rights that were established after 1994 in the Bill of Rights have not changed their lives and working conditions. These working conditions continue to affect them and are a risk to their physical and mental health. (Mohutsioa-Makhudud, 1989; Williams, 2008; Ally, 2009). The risk that is inherent in chronic perceived discrimination to one’s mental health (Mohutsioa- Makhudu ,1989:40) and the risk of developing a negative identity and self hatred by internalising the negative views of a dominant society(Phinney, 1989:34) has influenced the decision to do this research. The method of Narradrama chosen for this study was researched by Dunne (as cited in Leveton 2010) and found to be effective in working with marginalised groups but has not yet been researched with a marginalised stratum within the South African context. Narradrama, became the preferred method as it is centred on story (Dunne and Rand, 2013:7) which led to the thought it would be effective when working with a group of African women who are considered to be story tellers in the African culture. (Scheub, 1970: 119-120). Thematic data analysis was used in analysing the results. Identity shift was measured by comparing the change between the initial negative themed stories, that substantiated the hypothesis that participants do feel oppressed and marginalised, with the new, positive themes that appeared later in the research processes The Narradrama processes were analysed through the theoretical lens of Landy’s role theory, who proposes that for a person to have a healthier identity he needs to take on a variety on new roles, and to be able to play them proficiently. The playing of new roles assists participants to enlarge their perspectives, discover new identity descriptions and experience what it would feel like to move forward in life in preferred ways towards a more manageable, hopeful future. (Landy, 1994:93-97) This parallels the Narradrama notion which claims that by re-storying a client’s narrative, the client opens up to new preferred choices; a new landscape of identity and action (Johnson and Emunah, 2009:182). The research results show the start of a shift, in the participants’ re-authored stories and their assumed choices of new roles- these changes signify that the group has benefited from processes. As the researcher, I therefore recommend that these processes be resumed in order to allow these identity shifts inclusive of the suggested roles to become more substantial, and more integrated in the participants’ identity within their current living and working context. However, though Narradrama proved to be a method that can assist this group, the results of this research cannot be generalised, and further research with different groups of domestic workers will need to be done in order to be able to generalise to the wider context of the stratum of South African domestic workers.
Research report submitted to the Wits School of Arts University of the Witwatersrand, Faculty of Humanities In partial fulfillment of the requirements for the Degree of Master of Arts in the field of Drama therapy April 2016
Keywords: Drama--Therapeutic use; Narrative therapy; Arts--Therapeutic use; Women household employees--South Africa; Personal construct therapy